Study The Role of Some Liver Enzymes in Patient with Hepatitis in Karbala - Al-Khafaji, Muhammad F. D.; Jameel, Fatima K.; Trad, Narjes A. A.; Turkey, Ayat M.; Abdullah, Jasim A. A. (Scientific Journal of Medical Research, 2023)
The study was done in date 2022. In the public health laboratory. Twenty-nine samples were collected from the public health laboratory in Karbala from hepatitis patients with three types A, B, and C. These samples included 18 males and 11 females. The samples were then transferred to Imam Al-Hussein Teaching Hospital in Karbala for liver enzyme tests "GOT, GPT" to evaluate the value of these enzymes compared to ( the age and sex of patients ) with viral hepatitis. According to the findings, there is a strong correlation between age and viral hepatitis; the older you are, the more likely you are to contract type C and B infections. As for the results of the relationship of sex with liver enzymes for patients with viral hepatitis, during the study and research conducted for a period of no less than 5 months, there is no statistical significant at the p = 0.05.